P3.099 Sex Work as an Emerging Risk Factor For HIV Seroconversion Among Injection Drug Users in the SurvUDI Network. (13th July 2013) - Blouin, K; Leclerc, P; Morissette, C; Roy, É; Blanchette, C; Parent, R; Serhir, B; Alary, M
Abstract : Background: Previous analyses of SurvUDI data have shown an emerging positive association between sex work and HIV incidence among injection drug users (IDUs). Objective: To characterise the association between sex work and HIV seroconversion among IDUs in the SurvUDI network between 2004 and 2010. Methods: Participants who had injected in the past 6 months were recruited across the Province of Quebec and Ottawa, Canada, mainly in harm reduction programmes. They completed a questionnaire and provided saliva for HIV antibody testing. Multiple visits were linked through an encrypted identifying code. The association between sex work (defined as reporting at least one client sex partner in the last six months) and HIV seroconversion was tested with a Cox proportional hazards model. Time-dependent covariables tested as potential confounders were age (< 25 vs. ≥ 25 years), sex, cocaine as the most often injected drug, injection with strangers, injection with a needle previously used by someone else, and consistent condom use (defined as always using a condom for vaginal and anal sex with casual, client and paid sex partners, with no sex partners as reference category). Covariables were retained as confounders when they changed the adjusted hazard ratio (AHR) by > 10% when removed from the complete model. Results: Sixty-four HIV seroconversions were observed during 3020 person-years of follow-up. In the final multivariate model, HIV incidence was significantly associated with sex work (AHR = 1.94, 95% CI: 1.09–3.46, p < 0.03) and injection with a needle previously used by someone else (AHR = 3.13, 95% CI: 1.88–5.22, p < 0.0001), adjusted for age. Sex did not modify the association with sex work. Conclusion: Sex work is independently associated with HIV incidence among IDUs. Further studies are needed to understand whether this association is related to sexual transmission or if sex work is an intermediate variable between other unknown vulnerability factors and HIV transmission.